KOMPENSASI, LINGKUNGAN KERJA DAN KINERJA KARYAWAN (STUDI KASUS: RUMAH SAKIT IBU DAN ANAK ERIA BUNDA PEKANBARU) - Kusdiana, Yayu (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
The purpose of this study was to determine the effect of compensation and work environment on employees’ performance at RSIA Eria Bunda Pekanbaru. The method used in this research was quantitative descriptive method. The sample in this study were 55 people from 120 employees. The sample were taken by using random sampling (Random Sampling). The hypothesis in this study consist of F test, and T test. Based on F test result, it proved that compensation and work environment has significant effect to employee performance, indicated by value of Fcount which was bigger than Ftable (6,352 > 3,175). Based on T test proved that the compensation of work has not significant effect to employees’ performance which was shown by Tcount was bigger than Ttable (0,747 < 2,005) with significant level is 0,459 < 0,005. Work environment has significant effect to employees’ performance at RSIA Eria Bunda Pekanbaru. It was shown by Tcount value was greater than Ttable (3,367 > 2,005) with significant level is 0,001) < (0,005